2013
DOI: 10.1016/j.canep.2013.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Risk of adult acute and chronic myeloid leukemia with cigarette smoking and cessation

Abstract: Background Cigarette smoking is an established risk factor for adult myeloid leukemia, particularly acute myeloid leukemia (AML), but less is known about the nature of this association and effects of smoking cessation on risk. Methods In a large population-based case-control study of myeloid leukemia that included 414 AML and 185 chronic myeloid leukemia (CML) cases and 692 controls ages 20–79 years, we evaluated risk associated with cigarette smoking and smoking cessation using unconditional logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 32 publications
1
51
1
Order By: Relevance
“…In terms of lifestyle factors, cigarette smoking has been reported to increase the risk of myeloid leukemia, particularly AML (Musselman et al, 2013; Strom et al, 2012; Fircanis et al, 2014; Slager et al, 2014), while, in one study (Slager et al, 2014), an inverse association was found between current smoking and CLL. In the UK Million Women Study (Kroll et al, 2012), higher levels of smoking were associated with increased risk of MDS but not CLL.…”
Section: Introductionmentioning
confidence: 89%
“…In terms of lifestyle factors, cigarette smoking has been reported to increase the risk of myeloid leukemia, particularly AML (Musselman et al, 2013; Strom et al, 2012; Fircanis et al, 2014; Slager et al, 2014), while, in one study (Slager et al, 2014), an inverse association was found between current smoking and CLL. In the UK Million Women Study (Kroll et al, 2012), higher levels of smoking were associated with increased risk of MDS but not CLL.…”
Section: Introductionmentioning
confidence: 89%
“…Ionising radiation is the only established risk factor, having been linked to CML in atomic bomb survivors [32]. Results from a recent population-based case-control study suggested a weak association between smoking and CML, but this has not yet been confirmed by other studies [33]. In a study based on the Swedish Cancer Registry and Multigenerational Registry, Bjorkholm et al found no significant familial aggregation of CML [13].…”
Section: Risk Factors For Developing CMLmentioning
confidence: 97%
“…Only 0.11% (0.05%-0.26%) of inhaled benzene is metabolized to SPMA, which has a short half-life; mean ranges from 9 to 13 hours (39)(40)(41). Cigarette smoking is regarded as a source of benzene intake and an established risk factor for adult acute myelogenous leukemia (42)(43)(44)(45)(46)(47)(48)(49). Cigarette smokers have elevated excretion of SPMA, as much as ten times higher than non-smokers (50).…”
Section: Introductionmentioning
confidence: 99%